Decadence and indifferentiation in the ideology of the Front National. (May 2014) - Almeida, Dimitri
Decadence, moral decay and national disintegration are obsessively recurrent themes in the narratives of the French radical right. This article explores the topos of decadence in the Front National's ideology through a content analysis of speeches and campaign material ranging from the 1980s until 2012. Beginning with an interpretation of decadence based on René Girard's discussion of persecution-legitimising texts, the article argues that the Front National's discourse on decadence revolves around the idea of a crisis of differences and an acceleration of exchanges presented as unnatural. This point is developed in relation to the role of sexuality in the party's profile and to the logics of historical development and political agency inherent to the Front National's understanding of decadence. Decadence, I argue, is indissociable from indifferentiation – the fear of seeing the disappearance of differences conceived as fundamental for the preservation of national order.